Friction magazine: The upcycling of manufacture for structural design. Issue 4 (December 2021) - Le Pavec, Alexandre; Zerhouni, Sonia; Leduc, Nicolas; Kuzmenko, Kateryna; Brocato, Maurizio
The growing need for new buildings and the soaring resources depletion call for a new way of considering the building material. As follows, the principle of recycling and reuse keep gaining in consideration as a pertinent strategy to address those issues, inciting the use of new materials and approaches for structural design. The present paper inscribes in this later framework and proposes a method for structural design and manufacturing out of old magazines using a broadly known physical phenomenon of friction in interleaved assemblies. The proposed method consist of a stock-based form-finding strategy for a net-like structure, based on the mechanical and fabrication-aware considerations with an integration of a geodesic constrain control for the rectilinear paper strips. In closing, a demonstration pavilion is built using the developed method and its further potential applications in construction sector are discussed.